Penilaian Unjuk Kerja dalam Pembelajaran - Liansyah; Ubabuddin; pengelola, pengelola (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2023)
This development research has the main objective of producing valid, reliable and practical assessment tools or procedures. Performance appraisal instrument. In accordance with its understanding, it can be said that assessment is an activity of measuring, quantifying and determining the quality of student knowledge as a whole. In this sense it is implied that assessment must be integrated in the learning process and use various forms. Tests and assessment techniques are only needed to show how students do actual tasks. The performance assessment instrument developed consists of: (1) task items; (2) audio musical accompaniment; (3) scoring rubric; (4) observation sheets; and (5) guidelines for interpreting the results of the assessment.